2011
DOI: 10.3892/etm.2011.209
|View full text |Cite
|
Sign up to set email alerts
|

Association of a functional polymorphism (Gln261Arg) in 12-lipoxygenase with breast cancer

Abstract: Abstract. the overexpression of arachidonyl lipoxygenase-12 (alOx12) in breast cancer has been reported. hence, we examined whether a non-synonymous polymorphism of alOx12 (mrna, a835G; Gln261arg) is associated with breast cancer in females. the polymorphism was detected in genomic dna by pcr-rFlp. the association between the a835G polymorphism and breast cancer risk was measured by odds ratio (OR) with 95% confidence intervals (CIs) using Fisher's exact test, and differences were considered significant at p<0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Higher levels of 12-LOX were also observed in tumors from patients who died of breast cancer (30). Furthermore, a non-synonymous polymorphism of A12LOX (mRNA, A535G; gln261Arg) has been associated with increased risk of breast cancer, especially the Arg/Gln and Arg/Arg variants (31). In line with this, a recent preclinical study further documented that 12-HETE serves as a key mediator of tumor cell invasion into lymphatic vessels and formation of lymph node metastasis in ductal mammary carcinomas (32).…”
Section: Resultsmentioning
confidence: 99%
“…Higher levels of 12-LOX were also observed in tumors from patients who died of breast cancer (30). Furthermore, a non-synonymous polymorphism of A12LOX (mRNA, A535G; gln261Arg) has been associated with increased risk of breast cancer, especially the Arg/Gln and Arg/Arg variants (31). In line with this, a recent preclinical study further documented that 12-HETE serves as a key mediator of tumor cell invasion into lymphatic vessels and formation of lymph node metastasis in ductal mammary carcinomas (32).…”
Section: Resultsmentioning
confidence: 99%
“…The best-studied example includes mutation of E261R (835A>G), which causes an increase in 12-LOX activity, with a potential link to esophageal squamous cell carcinoma [64] . This mutation has also been associated with colorectal cancer [47,65] and breast cancer [48] . An in vitro and in vivo study has shown that 12-LOX plays a role in the proliferation and antiapoptosis of hepatocellular cells, suggesting that this carcinogenic function of ALOX12 requires endogenously generated lipid mediators [66] .…”
Section: -Lipoxygenase (12-lox)mentioning
confidence: 96%
“…These enzymes are expressed in leukocytes in humans and in platelets, megakaryocytes, and skin in mice [45,46] . Genetic studies have suggested that ALOX12 gene polymorphisms are associated with cancers [47,48] , neurological disorders [49,50] , hypertension [51,52] , fat mass [53] , and bone mineral density [54–57] . The mechanism of regulation of 12-LOX expression has been studied in several models.…”
Section: -Lipoxygenase (12-lox)mentioning
confidence: 99%
“…A recent meta-analysis found that polymorphisms in the ALOX12 gene at the Gln261Arg locus may influence cancer risk in Asian populations but not in Caucasians [ 60 ]. Furthermore, carriers of the variant in homozygous or heterozygous form had an increased risk for breast cancer, also demonstrating differences across ethnic populations [ 61 ]. The same polymorphism also showed an association with risk of colorectal adenomas [ 62 ].…”
Section: Genetic Polymorphisms Modulate Leukotriene Synthesis In Cmentioning
confidence: 99%
“…Limitations in these studies include recall bias in the FFQ and diet diaries, which are commonly used in large studies such as cohorts or case-control designs due to lack of affordable and better alternatives. Furthermore, ethnicity must be adjusted for in studies, as ethnicity may influence the relationship between dietary n -3 PUFA, cancer risk and genotype, as highlighted earlier [ 60 , 61 ]. Additional factors potentially influencing the outcome of the studies reviewed herein, include the stage of the disease, as LC n -3 PUFA may interact differently with genotypes as the physiology of the tumour changes, and fish contaminants.…”
Section: Prostaglandin Synthesismentioning
confidence: 99%